2021
DOI: 10.1002/mco2.65
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the structure–function relationship of human multidrug resistance protein 7 (MRP7/ABCC10) from molecular dynamics simulations and docking studies

Abstract: ATP‐binding cassette (ABC) transporters superfamily mediates multidrug resistance in cancer by extruding structurally distinct chemotherapeutic agents, causing failure in chemotherapy. Among the 49 ABC transporters, multidrug resistance protein 7 (MRP7 or ABCC10) is relatively new and has been identified as the efflux pump of multiple anticancer agents including Vinca alkaloids and taxanes. Herein, we construct and validate a homology model for human MRP7 based on the cryo‐EM structures of MRP1. Structure–func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The cryo‐EM structure of ABCC1 92 , ABCC8 93 were reported, while the information of other transporters are from X‐ray diffraction or remained unknown. Recently, a homology‐model‐based molecular dynamic study regarding ABCC10 was reported by our group 94 . Structurally, ABCC1‐3 and ABCC6/8/9/10 have an additional N‐terminal TMD (TMD 0 ) that is smaller than the core TMD 95 .…”
Section: Abc Transporter Subfamilies: Structure Function and The Rela...mentioning
confidence: 99%
“…The cryo‐EM structure of ABCC1 92 , ABCC8 93 were reported, while the information of other transporters are from X‐ray diffraction or remained unknown. Recently, a homology‐model‐based molecular dynamic study regarding ABCC10 was reported by our group 94 . Structurally, ABCC1‐3 and ABCC6/8/9/10 have an additional N‐terminal TMD (TMD 0 ) that is smaller than the core TMD 95 .…”
Section: Abc Transporter Subfamilies: Structure Function and The Rela...mentioning
confidence: 99%
“…In our study, we also found that MRP7 altered the cell morphology and promoted cell migration via upregulating the EMT marker N-cadherin. Although functionally active ABC transporters have generally been observed in both the cell membrane and intracellular vesicles, MRP7 in particular has been demonstrated earlier to exert its main effect at the cell membrane (49). The immunofluorescence assay and membrane/ cytoplasm protein immunoblotting showed that the MRP7 protein mainly localized on cell membrane.…”
Section: Discussionmentioning
confidence: 93%
“…(2) The overexpression of MRPs such as MRP1, MRP2, and MRP7 is associated with poor chemotherapeutic outcomes in several cancers including breast cancer and lung cancer. Among these MRPs, MRP1 has been widely studied in the development of therapeutic strategies for drug resistant cancer [73,74]. Resveratrol (RSV), which is a polyphenol comes from grape and Chinese medicine Rhizoma polygoni cuspidati, was found to downregulate the expression of MRP1 and P-gp in DOX-resistant breast cancer cells, promoting the accumulation of DOX in resistant cells and thus enhancing the effects of chemotherapy in MDA-MB-231/ADR tumor-bearing mice [75].…”
Section: Reversal Of Drug Resistancementioning
confidence: 99%